New lesion after endovascular therapy of femoropopliteal lesions for intermittent claudication. Issue 3 (21st May 2021) - Katsuki, Tomonori; Yamaji, Kyohei; Soga, Yoshimitsu; Iida, Osamu; Fujihara, Masahiko; Kawasaki, Daizo; Ando, Kenji
Abstract: Background: Although the incidence of target lesion revascularization (TLR) was decreased in patients who underwent endovascular therapy (EVT) for femoropopliteal (FP) lesions, the clinical impact of newly developed lesions could not be disqualified in those patients. Methods: Between January 2012 and December 2018, 911 patients with intermittent claudication (IC) who have not been previously treated for this condition underwent a successful EVT for de novo FP lesions in a multicenter registry (WATERMELON registry: neW lesion AfTer EndovasculaR therapy for interMittEnt cLaudicatiON). Results: The mean follow‐up duration was 3.5 ± 1.9 years. At 5 years, 53% patients underwent limb revascularization, (new lesion: 42% and TLR: 31%). We developed an ordinal risk score to predict the possibility of new lesion revascularization the following risk factors: body mass index (<23 kg/m 2, 1 point), diabetes (2 points), hemodialysis (3 points), and atrial fibrillation (2 points). The patients were divided into three groups: low risk group (0–1 points: N  = 283), intermediate risk group (2–3 points: N = 395), and high risk group (≥4 points: N  = 233). The cumulative 5‐year incidence of new lesion revascularization was 28% in the low risk group, 40% in the intermediate group, and 68% in the high risk group (p < 0.001). Conclusion: within 5 years after the first EVT, more than half of the patients underwent limb revascularization. Of these patients, 42% underwent new lesion revascularization. Patients with a body mass index <23 kg/m 2, diabetes, hemodialysis, and atrial fibrillation had increased risk for new lesion revascularization.